2015
DOI: 10.15570/actaapa.2015.9
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory diagnosis and epidemiology of herpes simplex 1 and 2 genital infections

Abstract: Herpes simplex virus types 1 and 2 are the main cause of genital ulcers worldwide. Although herpes simplex virus type 2 is the major cause of genital lesions, herpes simplex virus type 1 accounts for half of new cases in developed countries. Herpes simplex virus type 2 seroprevalence rises with sexual activity from adolescence through adulthood. Slovenian data in a high-risk population shows 16% seroprevalence of HSV-2. HSV-1 and HSV-2 DNA in genital swabs was detected in 19% and 20.7%, respectively. In most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…This difference was attributed to the HSV‐2 because HSV‐1 most commonly occur in children from 6 months to 3 years of age, and the infection rate keeps increasing until adolescence . Antibodies against HSV‐2 are rarely detected before adolescence and its seroprevalence rises with sexual activity from adolescence through adulthood . In addition, although the IgG proportion of HSV between male and female is not statistically significant according to Fisher's test, the age‐adjusted OR analyzed by logistic regression test indicated gender as a risk factor for HSV seropositive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This difference was attributed to the HSV‐2 because HSV‐1 most commonly occur in children from 6 months to 3 years of age, and the infection rate keeps increasing until adolescence . Antibodies against HSV‐2 are rarely detected before adolescence and its seroprevalence rises with sexual activity from adolescence through adulthood . In addition, although the IgG proportion of HSV between male and female is not statistically significant according to Fisher's test, the age‐adjusted OR analyzed by logistic regression test indicated gender as a risk factor for HSV seropositive.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, the seroprevalence of HSV IgM, in contrast to that of IgG, was significantly higher in <20 than ≥20 cohorts. This difference was attributed to the HSV‐2 because HSV‐1 most commonly occur in children from 6 months to 3 years of age, and the infection rate keeps increasing until adolescence . Antibodies against HSV‐2 are rarely detected before adolescence and its seroprevalence rises with sexual activity from adolescence through adulthood .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although HSV-2 is the major cause of genital lesions, HSV-1 accounts for half of new cases in developed countries. [ 16 ] In this study, all the isolates from genital ulcer were identified as HSV-2 and the lone isolate from oral blister was identified as HSV-1.…”
Section: Discussionmentioning
confidence: 90%
“…HSV-1 has been typically associated with oral lesions, while HSV-2 is the major cause of genital lesions. Recently more cases of HSV-1 genital herpes have been reported [30, 31]. Genital herpes is of concern during pregnancy because of the risk of transmission to the infant [31].…”
Section: Introductionmentioning
confidence: 99%